Case Report: rescue thrombolysis after failed primary percutaneous coronary intervention in coronary artery ectasia with ST-elevation myocardial infarction - Sun, Jiejun; Tang, Muyun; Zhang, Zhiyu; Yang, Ming; Shen, Zhujun; Tian, Ran; Liu, Zhenyu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary artery ectasia (CAE) is a rare disease characterized by pathological ectasia of the coronary artery. In the setting of ST-segment elevation myocardial infarction (STEMI), primary percutaneous coronary intervention (PCI) of the ectatic culprit vessel is less likely to succeed due to significant thrombus burden and tortuous ectatic coronary anatomy. However, there are currently no clinical guidelines for subsequent treatment when primary PCI fails. We present a case of successful revascularization by rescue thrombolysis after failed primary PCI in a CAE patient presenting with STEMI.Case presentationA 63-year-old male presented with a four-hour history of typical rest angina and electrocardiographic findings of inferior ST-segment elevation was diagnosed with acute inferior STEMI. Emergency coronary angiography revealed a complete mid-segment occlusion of the right coronary artery (RCA) and abnormal ectasia of the three main coronary arteries. Multiple attempts to cross the lesion with a guidewire were unsuccessful, leading to the termination of primary PCI. Subsequently, rescue thrombolysis was administered, and repeat angiography confirmed recanalization of the RCA.DiscussionThis case is the first to highlight the potential benefit of timely rescue thrombolysis in CAE patients with STEMI when primary PCI fails. It provides useful clinical insight into the management of this high-risk subset of STEMI patients.